2001
DOI: 10.1116/1.1420201
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated field emission devices using carbon nanofibers as cathode elements

Abstract: The digital electrostatic electron beam array lithography concept under development at the Oak Ridge National Laboratory proposes performing direct write electron beam lithography with a massively parallel array of electron emitters operating simultaneously within a digitally programmable microfabricated field emitter array (FEA). Recently we have concentrated our research efforts on the field emission (FE) properties of deterministically grown vertically aligned carbon nanofibers (VACNFs). We have measured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 11 publications
0
42
0
Order By: Relevance
“…Some radical and ionic species (e.g. C 3 H x , C 3 H y + ,…) as well as the negative ions are not incorporated in the model, although they might be present in a CH 4 plasma, but they have much lower densities. Note that the electron impact reactions are treated with energy dependent cross sections, whereas the ion and neutral reactions are described by rate coefficients.…”
Section: The Plasma Chemistry For Cnt/cnf Growthmentioning
confidence: 99%
See 4 more Smart Citations
“…Some radical and ionic species (e.g. C 3 H x , C 3 H y + ,…) as well as the negative ions are not incorporated in the model, although they might be present in a CH 4 plasma, but they have much lower densities. Note that the electron impact reactions are treated with energy dependent cross sections, whereas the ion and neutral reactions are described by rate coefficients.…”
Section: The Plasma Chemistry For Cnt/cnf Growthmentioning
confidence: 99%
“…Two-dimensional carbon nanowalls were deposited in CCP-PECVD with C 2 F 6 (CH 4 /CF 4 )/H 2 mixtures by Hiramatsu et al [16]. Indeed, the authors found that the carbon nanowalls grown using CH 4 /H 2 were waved and thin instead of vertically aligned.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations